Identification of tomato accessions (Solanum spp.) in the Vinces river basin – Ecuador - Medina Litardo, Reina Concepción; Pérez Almeida, Iris Betzaida; Sánchez Gonzales, Giannina Silvina; Navia Pesantez, Oscar Javier (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
The objective of this research was to characterize morphologically the wild accessions of tomato (Solanum lycopersicum) in the Vinces River basin - Ecuador for the establishment of a germplasm bank. Genetic material was collected; 10 accessions were chosen, and their seeds were obtained, from which the plants to be characterized were sown and technically managed. A randomized complete block design was set with ten treatments including the commercial control (Floradade), with 10 repetitions. The morphological characteristics evaluated were hypocotyl color, pubescence, type of leaf growth, internode length, inflorescence, mature fruit and seed characteristics, using the Bioversity International descriptors. The treatment that obtained the largest hypocotyl size was LR34 with 0.88 cm. The LR6 treatment presented a greater leaf length with 3.28 cm, and the LR18 treatment reached a greater width with 2.23 cm. In relation to the length of internodes, the treatment that presented the longest measurement was LR15 with 6.25 cm. The corollas in all the accessions were yellow and open. The LR1 treatment obtained longest fruit length with 14.28 mm, and with respect to width, the LR1 treatment presented a greater value of 61.13 mm. The treatment that presented the highest number of fruits per cluster was LR20 with 7.58 fruits. In this work, the main Solanum spp accessions in the studied area were morphologically characterized.
Keywords: biodiversity; descriptors; genetics; germplasm; wild tomato